Recent Evidence of Tea Tree Oil Effectiveness in Blepharitis Treatment. (30th July 2022) - Capasso, Luigi; Abbinante, Giulia; Coppola, Alessia; Salerno, Giulio; De Bernardo, Maddalena
Abstract : The purpose of our study is to see how beneficial is tea tree oil (TTO) for treating chronic blepharitis topically, with a focus on the Demodex mite. To discover all possibly relevant published papers, an accurate Pubmed database search analysis of the current literature was undertaken from 2012 to December 2021. Fourteen papers dealing with the use of TTO to treat chronic blepharitis have been found. The effectiveness of TTO treatment was tested in vitro by 4 authors and in vivo by 10 authors. All studied confirmed efficacy of TTO treatment, even cyclic, on Demodex mite blepharitis. TTO can be used for lid scrubs, facial cleanser, eyelid patch, eyelid gel, eyelash shampoo or, more commonly, as TTO impregnated eyelid wipes. The scientific evidence of TTO for chronic blepharitis treatment gives a lot of confidence for the progress that this treatment may have in the future clinical practice.